Withdrawing from treatment for Bladder cancer: Patient experiences of BCG installations. Issue 3 (10th June 2020) - Alcorn, Jason; Burton, Rob; Topping, Annie
Abstract: Research question: The aim of this study is to explore how the patient's experience of their treatment influence withdrawal from BCG? And what are the strategies that could reduce patient withdrawal from BCG treatment? Research problem: The cumulative treatment side effects of Bacillus Calmette‐Guerin can be both physical and psychological. Bladder cancer accounts for over 10 000 new diagnosis annually in the United Kingdom. Therefore, this article attempts to explore the patient's experience of their treatment and how this influences their withdrawal from treatment. Literature review: A literature review was undertaken utilizing the CONSORT approach for reporting of research trials. Multiple databases were searched. The review showed that there is a paucity in the literature in the comprehensive understanding of the patient's experience of undertaking BCG treatment and potential subsequent withdrawal. Methodology: A qualitative data was collected using semi‐structured interviews. Six interviews were conducted on participants who withdrew from intravesical BCG treatment. An inductive approach was used to thematically analyse the data. Results: NVivo 10 was used to manage the data. Following an in‐depth analysis of the interview transcripts when all available data had been extracted and coded, four key themes emerged. These four themes were identified as: "treatment concerns"; "withdrawal influencers"; "unmet needs"; and what appeared to be "treatment bereavement" were concerning to the participants. Conclusions: This article presents the results from the qualitative phase of a larger mixed methods study. The data produced from the interviews highlights themes and factors that cause patients to withdraw from BCG treatment early. These areas show the requirement for additional support in areas of communication, information giving and decision making. This study also identified a "novel" concept of "treatment bereavement", which described the feelings of loss when withdrawing early.